Empleo de rizobacterias como promotores de crecimiento vegetal en la asociacion del pasto festuca (Festuca arundinacea Schreb) con alfalfa ( Medicago sativa) y trebol rojo (Trifolium pratense) - Lopez Haro, Aida Gabriela (2012)
Pastures and fodder are the staple food of cattle and other grazing use efficiency could meet much of the nutritional requirements of livestock. This research was conducted in the parish of the canton Marcos Espinel Píllaro Tungurahua province lasted 60 days as a general objective determine the microbial population in the association of grasses and legumes by inoculation of plant growth promoting rhizobacteria and specifically targeted Inoculate the plant growth promoting rhizobacteria: chroococum Azotobacter, Azotobacter vinelandii, Azotobacter and Pseudomonas beijerinckii paspali fluorescens in grass-legume associations in study, using a completely randomized design (CRD) with two associations of grasses, five inoculants and two crop ages . In the corresponding interaction grass + legume inoculants x age legume root length (cm) in which it is observed that after 45 days with the grass Festuca + and Trébol Alfalfa with the inoculant A. 20.67 and 22.67 with Chroococum cm followed by the inoculant P. fluorescens (21.00 and 23.00 cm) and Witness (20.00 and 22.33 cm) to the investigation by the grass root length (cm) at Pasto interaction + legume inoculants x age x can be seen that there is interaction at 45 days with the grass Festuca + + Alfalfa and Clover and inoculant A. 16.33 and 16.67 with beijerinckii cm followed by P. fluorescens (24.33 and 26.00 cm) at 60 days and control (20.67 and 21.00 cm) at 45 days. Based on the weight of roots can be seen that within the interaction results in the Grass & Legume x inoculant x age interaction is reflected in the grass Festuca + + Alfalfa and Clover at 60 days with the inoculant A. with 2.83 and 3.17 chroococum g, followed by inoculating A. beijerinckii at 45 and 60 days (2.50 and 3.00 g) (2.17 and 2.67 g) respectively and the inoculant Witness with 1.67 and 2.00 g Interaction Legume Grass + x inoculant x age in grass root weight (g) reflects the grass Festuca interaction and Festuca + + Alfalfa Clover 60 days with the inoculant A. beijerinckii with 4.33 g respectively Witness inoculant followed by 60 days with 3.00 and 317 g, and in turn forage legume Weight (g) In research conducted at the Grass & Legume inoculants x age x can be seen that there is statistical similarity Alfalfa grass and fescue Festuca + + Trébol at 60 days with the inoculants with 4.17 and 4.83 Witness g.